Pemberdayaan Masyarakat Desa Krajan Melalui Budidaya Jamur Tiram Mewujudkan Desa Tanpa Kemiskinan - Muhamad Firmansyah; Siti Muntahanah Ana; Esti Ningrum Esti (LPPM IT Telkom Purwokerto, 2025)
The Community Service Program in the form of Community Empowerment by Students (KKN-PMM), funded by the Directorate of Research and Community Service (DPPM) KemenristekDIKTI for the 2025 fiscal year, aims to enhance welfare and address socio-economic issues in Krajan Village, Pekuncen, through the development of oyster mushroom cultivation enterprises. This program is implemented to assist the